Regional Pediatric Acute Stroke Protocol: Initial Experience During 3 Years and 13 Recanalization Treatments in Children. Issue 8 (August 2017) - Tabone, Laurence; Mediamolle, Nicolas; Bellesme, Celine; Lesage, Fabrice; Grevent, David; Ozanne, Augustin; Naggara, Olivier; Husson, Beatrice; Desguerre, Isabelle; Lamy, Catherine; Denier, Christian; Kossorotoff, Manoelle
Abstract : Background and Purpose—: To evaluate hyperacute management of pediatric arterial ischemic stroke, setting up dedicated management pathways is the first recommended step to prove the feasibility and safety of such treatments. A regional pediatric stroke alert protocol including 2 centers in the Paris-Ile-de-France area, France, was established. Methods—: Consecutive pediatric patients (28 days–18 years) with confirmed arterial ischemic stroke who had acute recanalization treatment (intravenous r-tPA [recombinant tissue-type plasminogen activator], endovascular procedure, or both) according to the regional pediatric stroke alert were retrospectively reviewed during a 40-month period. Results—: Thirteen children, aged 3.7 to 16.6 years, had recanalization treatment. Median time from onset to magnetic resonance imaging was 165 minutes (150–300); 9 out of 13 had large-vessel occlusion. Intravenous r-tPA was used in 11 out of 13 patients, with median time from onset to treatment of 240 minutes (178–270). Endovascular procedure was performed in patients time-out for intravenous r-tPA (n=2) or after intravenous r-tPA inefficiency (n=2). No intracranial or peripheral bleeding was reported. One patient died of malignant stroke; outcome was favorable in 11 out of 12 survivors (modified Rankin Scale score 0–2). Conclusions—: Hyperacute recanalization treatment in pediatric stroke, relying on common protocols and adult/pediatric ward collaboration, is feasible. Larger systematic case collection is encouraged. Abstract : Supplemental Digital Content is available in the text.